Vermeer's skopos theory and its application to the Arabic translation of Miller's Death of a Salesman - Jabak, Omar Osman; Syed Abdullah, Syed Nurulakla (Penerbit UTM Press, 2017)
The present study aimed at shedding some light on Vermeer's (1989) Skopos theory in translation as suggested by Vermeer along with the application of this theory to an English literary text taken from Miller's Death of A Salesman (1947) and its Arabic translation done by a Syrian Arab translator called Omar Jabak. Besides, the article will try to examine the weaknesses of Skopos theory in terms of its applicability to literary texts in particular. The researchers adopted the analytical descriptive approach in this small-scale qualitative study to prove the inapplicability of the Skopos theory principles to the above-mentioned English play and its Arabic translation. The research data and findings revealed that Vermeer's Skopos theory had somehow little applicability to translated literary works because literature and its translation, in general, and drama, in particular, have meaningful or 'skopos' in people's social, economic and political lives.